Theoretical Study of Diels-Alder Reaction of But-3-en-2-one with Hexa-1,2,4-triene: A Density Functional Theory Study - Rezan J. Hassan; Hassan H. Abdallah (ARO-The Scientific Journal of Koya University, 2020)
The Diels-Alder reaction between but-3-en-2-one with hexa-1,2,4-triene was studied using density functional theory method at B3LYP-D3/6-311++G(d,p) level of theory. The geometries of the transition states were determined. Moreover, calculations of the vibrational frequencies permitted computation of the activation enthalpies and entropies. The computational results show that the cycloadducts from trans conformer have the lower relative energies (−46.48 and −47.50 kcal/mol) as compared to the cis conformer of cycloadducts (−44.45 and −45.87 kcal/mol). The global reactivity indices were analyzed at the ground state of reactants to predict the reactivity of the studied organic molecules in the cycloaddition reactions. The electronic chemical potential of hexa-1,2,4-trien found to be than but-3-en-2-one, which indicates that the net charge transfer will be from hexa-1,2,4-trien toward the electron-deficient but-3-en-2-one reactant.